2006
DOI: 10.3892/or.16.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Role of p16 and p14ARF in radio- and chemosensitivity of malignant gliomas

Abstract: In addition to cytoreductive surgery, most patients with malignant gliomas also undergo radio-and chemotherapy. An improved understanding of the molecular genetic mechanisms underlying the radio-and chemosensitivity of gliomas may help to identify glioma patients who will benefit from aggressive and, therefore, potentially toxic adjuvant treatment. It may also allow for the development of new therapies aimed at improving the response of these tumors towards chemo-and radiotherapy. The INK4a gene products, p16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…INK4A expression as radiosensitizer, whereas p14 ARF expression rendered radioresistance in glioma cell lines (25). Our observation also points to such an inference, supporting a role for p16 INK4A and p14 ARF as modulators of radioresponse in oral cancer.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…INK4A expression as radiosensitizer, whereas p14 ARF expression rendered radioresistance in glioma cell lines (25). Our observation also points to such an inference, supporting a role for p16 INK4A and p14 ARF as modulators of radioresponse in oral cancer.…”
Section: Discussionsupporting
confidence: 65%
“…A study by Ogi et al is the only available report that observed an association between p14 ARF methylation and better survival in carcinoma cases but they were unable to arrive at a conclusion for such a result (24). A recent report on glioma supports the role of p14 ARF as modulator for radioresistance (25). As radiation is the main mode of treatment in our patients, the absence of p14 ARF might be rendering the tumor cells more sensitive to radiation.…”
Section: Ink4amentioning
confidence: 93%
“…However, different studies of the relationship between the p16 gene and chemosensitivity have not always obtained the same results. [39][40][41][42][43] In a nasopharyngeal carcinoma (NPC) cell line, p16 transfection resulted in increased sensitivity to cisplatin and 5-FU, and p16 reduced NPC cell growth through G0/G1 arrest and modulation of the cellular response to chemotherapeutic drugs in NPC cells. 39 In a glioma cell line, p16 and p14ARF were modulators of radio-and chemosensitivity to vincristine and BCNU (carmustine).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of c-raf-1 is positively correlated with radioresistance of head and neck squamous cell carcinomas (Dritschilo et al 2006), and p16 and p14ARF have also been suggested as potential regulators of glioma chemo-and radiosensitivity (Simon et al 2006). Radiotherapy is typically applied in a course of multiple fractions over several weeks (Ogawa et al 2006a).…”
Section: Introductionmentioning
confidence: 99%